Rheumatoid arthritis in a rural South African Negro population. Issue 2 (April 1975) - Beighton, P; Solomon, L; Valkenburg, H A
Abstract : (1) An epidemiological study of a rural African community has been carried out in the Western Transvaal. Altogether 801 respondents over 15 years old were examined; radiographs of the hands and feet were obtained in all these individuals. Serological tests for rheumatoid factor were carried out on 516 blood samples. (2) The diagnosis of inflammatory polyarthritis was based on a modification of the Rome Criteria of 1961. Two categories were defined: 'definite' and 'probable' rheumatoid arthritis. (3) In this population inflammatory polyarthritis was much less common and much milder in its manifestations than in European and American peoples. The prevalence of 'definite' rheumatoid arthritis was 0.12% and of 'definite' and 'probable' rheumatoid arthritis combined, 0.87. Such changes as were encountered on clinical and radiological examination were invariably mild; no respondent in the entire survey had clinical features that would have been accepted in the ordinary way as those of rheumatoid arthritis. (4) The latex fixation test (LFT) was positive in 8.9% of the sera tested; the modified LFT aftaer inactivation of the serum at 56 degrees C was positive in 15.1% of cases. Similar findings in West African populations have been explained on the basis of alteration of the immune response by widespread parasitic infections. No obvious aetiological factor of this type was found in the present survey.